ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MOTIVASI KERJA (Bank Jateng Cabang Pembantu Pasar Induk Kramat Jati Jakarta) - Bambang Bernanthos; Ani Sulistiasih (Jurnal Manajemen FE-UB, 2020)
This study aims to examine and analyze the influence of factors related to EmployeePerformance. These factors include Career Development and Training, which later in this studyfunctioned as independent variables that affect Employee Performance that functions as thedependent variable, while Work Motivation is a variable that functions as an intermediaryvariable (Intervening). The research method used in this study is path analysis.The results showed that there was a direct influence of Career Development and Trainingboth simultaneously and partially on work motivation. Career Development, Training and workmotivation directly influence Employee Performance both simultaneously and partially. Workmotivation as an intervening variable is able to mediate the indirect effect of CareerDevelopment and Training on employee performance, with the results of an appropriate modelsuitability test.Keywords:career development, training, work motivation, employee performance